SAFE CITY PROGRAMME: ARE WE ON THE RIGHT PATH TO REDUCE CRIME? - Shamsudin, Kamalruddin (PLANNING MALAYSIA, 2008)
Generally all types of property crime showed increase in occurrences; snatch theft showed a positive decline from 2004 to 2006 and stabilized in 2007. The safe city programme originated with the aim of putting across measures or steps that local authorities (PBTs) could implement immediately to reduce crime occurrences. Effectiveness of CCTV showed mixed result. Lessons from accredited safe city elsewhere (in particular Melbourne) suggest possible future directions for the safe city programme in Malaysia.